Assessment of MRI Contrast Agent Kinetics via Retro-Orbital Injection in Mice: Comparison with Tail Vein Injection - Wang, Fang; Nojima, Masanori; Inoue, Yusuke; Ohtomo, Kuni; Kiryu, Shigeru (PLOS ONE, 2015)
It is not known whether administration of contrast agent via retro-orbital injection or the tail vein route affects the efficiency of dynamic contrast-enhanced magnetic resonance imaging (MRI). Therefore, we compared the effects of retro-orbital and tail vein injection on the kinetics of the contrast agent used for MRI in mice. The same group of nine healthy female mice received contrast agent via either route. An extracellular contrast agent was infused via the tail vein and retro-orbital vein, in random order. Dynamic contrast-enhanced MRI was performed before and after administering the contrast agent. The contrast effects in the liver, kidney, lung, and myocardium were assessed. The average total times of venous puncture and mounting of the injection system were about 10 and 4 min for the tail vein and retro-orbital route, respectively. For all organs assessed, the maximum contrast ratio occurred 30 s after administration and the time course of the contrast ratio was similar with either routes. For each organ, the contrast ratios correlated strongly; the contrast ratios were similar. The retro-orbital and tail vein routes afforded similar results in terms of the kinetics of the contrast agent. The retro-orbital route can be used as a simple efficient alternative to tail vein injection for dynamic contrast-enhanced MRI of mice.